A study on etiology, clinical profile and outcome of acute febrile encephalopathy in children: A prospective study at a tertiary care center of Eastern India - Biswas, Rupa; Basu, Kaushambi; Tripathi, Ishita; Roy, Sunetra Kaviraj (Asian Journal of Medical Sciences, 2021)
Background: Acute febrile encephalopathy (AFE) is defined as fever associated with acute alteration of consciousness, with or without seizure, motor and/ or sensory deficit and total duration of illness one week or less. It is associated with significant morbidity and mortality in children. Various etiologies have been implicated in its causation and differ as per geographical. Efforts to promptly identify the underlying etiology and institute appropriate treatment early and adequately should be our goal so as to avoid any long-term sequelae and death. Aims and Objectives: To evaluate the clinical profile and aetiology of children presenting with fever and altered sensorium and to assess the predictors of morbidity & mortality related to Acute Febrile Encephalopathy. Materials and Methods: In this prospective, hospital-based study, a total of 282 children, between 1month to 12 years, presenting to the department of Pediatric Medicine, Calcutta National Medical College, Kolkata, West Bengal, India with fever and altered sensorium were clinically evaluated and investigated. Each patient was examined for vital signs, detailed systemic examination with focus on neurological examination. The etiology of AFE was evaluated based on detailed history, a meticulous clinical examination and relevant investigations. Results: The incidence of AFE was 5% of the total hospital admissions. Demographic profile showed 166 (58.8%) males, 116 (41.2%) females and 48% of the study population less than 5 years of age. The most important presenting complaints apart from fever and altered sensorium, were convulsion and vomiting. Raised Intracranial tension (58%), low GCS (58%) and shock (48%) were commonest presenting signs. CNS infections were the most common cause of AFE encountered. Low GCS, refractory seizures, multi-organ failure respiratory failure were significantly associated with death (p<0.005). Conclusions: CNS infections are the leading cause of febrile encephalopathy. Toxic- metabolic and unknown etiologies contributed maximum to the mortality. Low GCS, shock, refractory seizures, multi-organ failure and respiratory failure are associated with higher risk of mortality. Most of the morbidities were observed in auto-immune encephalitis and ADEM and as most of them were curable, early institution of appropriate treatment will decrease morbidity.